Technical report writing today - Riordan, Daniel; Pauley, Steven E. (New Delhi Biztantra, 2004)
Technical Report Writing Today provides thorough coverage of technical writing basics, techniques, and applications. Through a practical focus with varied examples and exercises, students internalize the skills necessary to produce clear and effective documents and reports. Project worksheets help students organize their thoughts and prepare for assignments, and Focus boxes highlight key information and recent developments in technical communication. Extensive individual and collaborative exercises expose students to different kinds of technical writing problems and solutions. Annotated student examples--more than 100 in all--illustrate different writing styles and approaches to problems. Numerous short and long examples throughout the text demonstrate solutions for handling writing assignments in current career situations. The four-color artwork in the chapter on creating visuals keeps pace with contemporary workplace capabilities. The Ninth Edition offers the latest information on using electronic resumes and documenting electronic sources and Ethics and Globalization sidebars that highlight these two important topics in the technical communication field.